Contract Workers and Outsourcing Protection at Batam Municipality Shipyard - Triyono Triyono (Jurnal Penelitian Kesejahteraan Sosial, 2016)
Working relationship and outsourcing contract custo marily encountered in the practice of employment. It is bringing implication of various problem especially relating to the proctection of labour. This arcticle will analyze the issues andproblems with the protection of labour and outsourcing contract especially wages, union right, health and safety of shipyard industry workers in Batam City. This study used a qualitative approach, done through in-indept interviews, focus group discussions, and observation. The result suggest that the protection of contract and outsorced workers in shipyard industry in Batam City still not protected thoroughly from the wages and freedom union, and safety protection. Given these problems, a solution of the increased intensity of supervision of the fulfillment of the right of protection labour is needed.